Modern Methods and Techniques in Landscape Shaping with Various Functions on the Example of Southern Poland - Boguslawa Kwoczynska; Urszula Litwin; Izabela Piech (Applied Sciences, 2022)
The aim of this publication is to present the detailed results of research on the formation of landscapes with different functions. The research was conducted in areas typical for southern Poland in Kasinka Mala and Kamionka Wielka communes using the WIT statistical method and photogrammetric techniques. Among the landscape evaluation methods, the publication uses the WIT method of site significance indices, which employs a wide representation of features describing the spatial structure of villages. Using these indicators, the “value” and changes that have occurred in the landscape of each designated area were assessed. Three indicators were determined: WIT 1—for agricultural activities, WIT 2—for non-agricultural activities, and WIT 3—for recreational activities, for each of the villages of the Kamionka Wielka commune, comparing them in a tabular and graphical form. The indicators were used to determine the suitability of the land for agricultural activities, its potential for economic activity, and the development of recreational and tourist activities in the area. Most of the factors determining the character of a landscape can be properly captured using photogrammetric and remote-sensing materials. Thanks to the technological advances provided by photogrammetric methods, visualizations of landscapes with different functions were also used in this study. For landscape analysis, photogrammetric materials in the form of aerial photographs, digital orthophotomaps taken in different time periods (1963–1977–1997–2010–2013), and data from airborne laser scanning were used, which allowed visualization of the studied areas in the form of a DSM and 3D models of Kasinka Mala and Kamionka Wielka.